Pathology Of Political Parties Towards 2024 Election Year - Hawari, Alhilal Yusril; Suwaryo, Utang; Kartini, Dede Sri (Pusat Riset Politik BRIN, 2023)
This research aims to discover the pathologies or diseases in political parties significantly ahead of the 2024 election year—taken from many sources, both unwritten and written sources from what has been obtained by researchers sourced from written data. The technique of collecting data in this study uses documentation or is called (Library Study), makes quotations, and performs data analysis with this Documentation Technique, such as books, journals, and other written sources. The results of this study explain that political parties in Indonesia have various pathologies or diseases, both in terms of party bodies and cadres within the party, which can affect the life of democracy for the people of Indonesia. The pathology of political parties can be resolved with the presence of cadres in political parties, improving party financial management and education for political party cadres.